Legal socialization and compliance to the islamic family law on maintenance among muslims in Selangor, Malaysia - Hasbullah, Muslihah; Jamaludin, Nurul Nadia; Kahar, Rojanah; Arshat, Zarinah (Human Resource Management Academic Research Society, 2023)
The alarmingly high number of divorces among Malaysians was brought on by a failure to uphold legal obligations and rights throughout marriage. Failure to fulfil marital obligations worsened following divorce, as evidenced by incidents of non-compliance with the Syariah Court orders on post-divorce financial supports. These failures are a reflection of how Muslims view family law, which affects how they behave. Legal socialization has been cited by earlier scholars as one of the developmental processes that would affect the pattern of individuals socialization and help shape legal attitudes and law-abiding behaviour. The Western setting has produced a wealth of literature on legal socialization, in which criminology dominated the majority of studies. Little is known about Malaysians' legal socialization within the context of Islamic family law and how they adhere to the law on family maintenance. The purpose of this study is to evaluate the legal socialization of individuals, their compliance with Islamic family law, and the associations between different facets of legal socialization and compliance among married and divorced Muslims in the State of Selangor. Four instruments on legal socialization (legitimacy of the law, procedural justice, legal cynicism, moral disengagement), and a self-report of compliance behavior were adapted from previous studies by Fagan and Tyler (2005) and Bandura et al. (1996). Findings show that the respondents have a high level of legitimacy of the law and procedural justice and a low level of legal cynicism and moral disengagement. Respondents’ positive experience with procedural justice have been found significantly related to their compliance behaviour. Hence, advocacy efforts to increase legal literacy on family rights and obligations among Muslims must be intensified at all levels, realizing the impact of legal socialization to uphold legal obligations towards the family.